Reduced expression in preterm birth of sFLT-1 and PlGF with a high sFLT-1/PlGF ratio in extracellular vesicles suggests a potential biomarker - Hussein, Sama; Ju, Weina; Pizzella, Stephanie; Flory, Michael; Chu, Chu; Wang, Yong; Zhong, Nanbert (Frontiers in Endocrinology, 2022)
Preterm birth may have a pathological impact on intrauterine development of fetal brain to result in developmental disabilities. In this study we examine the expression of soluble Fms-like tyrosine kinase 1 (sFLT-1) and placental growth factor (PlGF) that is one of vascular endothelial growth factors (VEGFs), as they play a key role in angiogenesis and their effect on the sFLT-1/PlGF ratio in preterm birth against normal pregnancies. Enzyme-linked immunosorbent assay was performed on 17 preterm and 38 controls case using maternal-derived plasma and extracellular vesicles-exosomes (EVs-EXs) isolated at the 3rd trimester samples. Our results showed that both sFLT-1 (P=0.0014) and PlGF (P=0.0032) were significantly downregulated in preterm birth compared to control, while the sFLT-1/PIGF ratio was significantly (P=0.0008) increased in EVs-EXs, but not in maternal plasma. Our results suggested that the lowered expression of sFLT-1 and PlGF with an increased ratio of sFLT-1/PlGF in EVs-EXs may present a potential biomarker for prediction of PTB.